ФОРМУЛА КАРЛЕМАНА ДЛЯ МАТРИЧНОГО ПОЛИКРУГА В ПРОСТРАНСТВЕ КОСОСИММЕТРИЧНЫХ МАТРИЦ - Матякубов, З.К.; Халкназаров, А.М. (SCIENCE and SOCIETY, 2024)
Carleman’s formula allows one to reconstruct the values of holomorphic or harmonic functions in a domain from their values in sets of singularities. In this paper, we prove Carleman’s formula on the unit polydisk for skew-symmetric matrices.